2019
DOI: 10.3389/fpls.2019.00138
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches to Optimize Somatic Embryogenesis in Maritime Pine

Abstract: Maritime pine ( Pinus pinaster Aiton) is a coniferous native of the Mediterranean basin. Because of its adaptability to a wide range of environmental conditions, the species have become a model for studies in coniferous forest management and functional genomics. Somatic embryogenesis (SE) has been so far, the preferred biotechnological strategy for maritime pine breeding programs initiated at the middle-end of the 20th century. To overcome the limitations of the induction and maturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 75 publications
7
26
0
Order By: Relevance
“…Although not significant, the number of Se’s increased under high temperatures, a long-observed trend in our laboratory for both P. radiata and P. halepensis EMs initiated under high temperatures ( García-Mendiguren et al, 2016b ; Castander-Olarieta et al, 2019 ; Pereira et al, 2020 ). The same pattern was detected in similar temperature-based experiments during initiation of Pinus pinaster SE ( Arrillaga et al, 2019 ), confirming the role of temperature as an activator of embryo development. On top of that, Castander-Olarieta et al (2019) reported altered morphologies in both EMs and Se’s originating from different temperature treatments, and despite not observing germination and acclimatization differences, the resulting somatic plants showed changes at phenotypic level in terms of growth and stress-resilience ( Castander-Olarieta et al, 2020a ).…”
Section: Discussionsupporting
confidence: 80%
“…Although not significant, the number of Se’s increased under high temperatures, a long-observed trend in our laboratory for both P. radiata and P. halepensis EMs initiated under high temperatures ( García-Mendiguren et al, 2016b ; Castander-Olarieta et al, 2019 ; Pereira et al, 2020 ). The same pattern was detected in similar temperature-based experiments during initiation of Pinus pinaster SE ( Arrillaga et al, 2019 ), confirming the role of temperature as an activator of embryo development. On top of that, Castander-Olarieta et al (2019) reported altered morphologies in both EMs and Se’s originating from different temperature treatments, and despite not observing germination and acclimatization differences, the resulting somatic plants showed changes at phenotypic level in terms of growth and stress-resilience ( Castander-Olarieta et al, 2020a ).…”
Section: Discussionsupporting
confidence: 80%
“…The metAFLP is a choice for studies involving different aspects of tissue cultures. One such issue is the optimisation of plant regeneration via somatic embryogenesis [ 49 , 50 ], which could be performed if an adequate statistical approach is used to simultaneously cope with many factors and minimize experimental efforts [ 51 ]. The Taguchi approach [ 52 ] of experimental design optimisation could be considered for such purposes.…”
Section: Introductionmentioning
confidence: 99%
“…SE, the inducible process of obtaining multiple embryos from vegetative (somatic) cells, is the most promising vegetative propagation technology for conifers worldwide [25,26], since these species typically lack the capacity to be efficiently propagated using low-cost techniques (e.g., cuttings). SE protocols have been developed by our group [27,28] for maritime pine (Pinus pinaster Aiton), a species widely used for afforestation in the North-western Mediterranean area due to its fast growth, and the quality of its timber and oleoresins, as well as to its high phenotypic plasticity and stress tolerance. Furthermore, in Spain large genetic variation in adaptive traits have been found between maritime pine provenances [29,30].…”
Section: Introductionmentioning
confidence: 99%